Effect of type 1 diabetes on school performance in a dynamic world: new analysis exploring Swedish register data. Issue 24 (21st May 2019) - Persson, Emma; Persson, Sofie; Gerdtham, Ulf-G.; Steen Carlsson, Katarina
ABSTRACT: This paper investigates if the effect of type 1 diabetes mellitus (T1DM) on school performance, documented in prior research, has changed in more recent birth cohorts of children using national Swedish population register data. The issue is of interest because management and treatment of the disease have improved over the last decades and, furthermore, because of changes in the educational grading system. Despite these changes, data indicate a persistent negative effect of T1DM on compulsory and upper secondary school grades with a standardized effect size of −0.109 and −0.070, respectively, and the results appear only marginally smaller compared to earlier findings in cohorts completing school under the previous grading system. Moreover, the results are consistent for alternative model specifications and econometric estimation strategies. Whereas access to new treatment technologies and improved diabetes management strategies has reduced the burden of diabetes in daily life, the results from this study indicate that continued efforts are needed to improve the situation in school for children with T1DM to prevent potential long-term socio-economic consequences.